KEANEKARAGAMAN FUNGI MIKORIZA ARBUSKULA PADA RIZOSFER VEGETASI TEMBAWANG SUALAM KECAMATAN MANDOR KALIMANTAN BARAT - sari, indah sartika; Ekamawanti, Hana Artuti; Wahdina, . (Universitas Tanjungpura, 2017)
The aim of this research is to find out the diversity of AMF (Arbuscular Mycorrhizal Fungi) species that grow onÂ tembawang Sualam vegetation in the Landak District of West Kalimantan. Sampling was conducted using a survey method with purposive sampling technique. Primary data included the number of spores, spore types, and infection AMF in the example root, while secondary data includes pH, temperature, soil temperature, air humidity, diameter, and height. The observation of the spores in soil samples revealed 6253 spores which consisted of nine types / spore types, 1,329 spores of Glomus sp. 1; 478 spores of Glomus sp. 2; 519 spores of Glomus sp. 3; 549 spores of Glomus sp. 4; 930 spores of Glomus sp. 5; 73 spores of Glomus sp. 6; 718 spores of Glomus sp. 7; 688 spores Acaulospora sp. 1 and 969 spores Acaulospora sp. 2. AMF colonization on the roots of the vegetation sungkut tu'ut (Oroxylum indicum), rambutan (Nephelium lappaceum), tan (Lansium domesticum), jengkol (Archidendron pauciflorum) and rubber (Hevea braziliensis) showed that a fifth of these plants gives host to AMF. Rubber and rambutan showed a low rate of colinization, sungkut tuâ€™ut and jengkol at moderate rates, with tan showing the highest rates of colinization. Diversity spores in the rhizosphere vegetation tembawang included low to moderate categories with the spread of spores and similarities in the rhizosphere sungkut tu'ut and tan more equally than the three other plant species. The composition of spores varied between species with only sungkut tuâ€™ut and tan showing similar compositions of dominate spores. Keyword: Arbuscular Mycorrhizal Fungi, Biodiversity, Tembawang